PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN DIVISI TI DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING - Riana, Dwi; Rianty, Martha (Balance : Jurnal Akuntansi dan Bisnis, 2019)
This research was conducted to determine the effect of the application of accounting information systems on the performance of IT division employees with organizational commitment as a variable intervening. This research was conducted at the Palembang State-Owned Bank consisting of Bank Negara Indonesia, Bank Republik Indonesia, Bank Tabungan Negara, and Bank Mandiri. The primary data collection technique was conducted by survey method distributing questionnaires. The population of this study were all employees of the Information Technology Division of the Palembang City State Bank, amounting to 56 people and the sample used was 56 people using a census that is all the population used as samples. Data Analysis using PLS is a part, as well as an alternative to SEM. From the results of calculations and analyzes carried out, the conclusion is that there is no influence between the application of accounting information systems to the performance of employees of the IT division of the state-owned Bank of Palembang.